Pomegranate peel extract prevents liver fibrosis in biliary-obstructed rats - ERCAN, FERİHA; ŞENER, GÖKSEL (WILEY, 2007)
Punica granaturn L. (pomegranate) is a widely used plant that has high nutritional value. The aim of this study was to assess the effect of chronic administration of pomegranate peel extract (PPE) on liver fibrosis induced by bile duct ligation (BDL) in rats. PPE (50 mg kg(-1)) or saline was administered orally for 28 days. Serum aspartate aminotransferase (AST), alanine aminotransferase (ALT) and lactate clehydrogenase (LDH) levels were determined to assess liver function and tissue damage. Proinflammatory cytokines (tumor necrosis factor-alpha and interleukin 1 beta) in the serum and antioxidant capacity (AOC) were measured in plasma samples. Samples of liver tissue were taken for measurement of hepatic malondialdehyde (MDA) and glutathione (GSH) levels, myeloperoxidase (MPO) activity and collagen content. Production of reactive oxidants was monitored by chemiluminescence assay. Serum AST, ALT, LDH and cytokines were elevated in the BDL group compared with the control group; this increase was significantly decreased by PPE treatment. Plasma AOC and hepatic GSH levels were significantly depressed by BDL but were increased back to control levels in the PPE-treated BDL group. Increases in tissue MIDA levels and MPO activity due to BDL were reduced back to control levels by PPE treatment. Similarly, increased hepatic collagen content in the BDL rats was reduced to the level of the control group with PPE treatment. Thus, chronic PPE administration alleviated the BDL-induced oxidative injury of the liver and improved the hepatic structure and function. It therefore seems likely that PPE, with its antioxidant and antifibrotic properties, may be of potential therapeutic value in protecting the liver from fibrosis and oxidative injury due to biliary obstruction.
Keywords: ANTIOXIDANT ACTIVITY; OXIDATIVE-STRESS; CYTOKINES; DAMAGE; ACTIVATION; SILYMARIN; TOXICITY; PROTEIN; PLASMA; INJURY